The scope of the principle of contributive capacity in the ecuadorian legal tax regime - Alcaciega-Ochoa, Lizbeth (2023)
The main objective of the research was to determine the importance of the principle of contributive capacity in the national legal tax system, in order to contribute to avoid the affectation to the patrimony of the taxpayers, and at the same time the proliferation of elusive and evasive figures in the face of the excessive taxation. With the 2008 Constitution, the tax system is governed by principles that set the basis for the creation, modification and extinction of taxes, which are established in Article 300, in which, although the principle of contributive capacity is not expressly included, it is immersed in the tax principles of equity and progressiveness. Therefore, the legislator will determine the taxpayer’s taxpaying capacity. This research applies the qualitative methodological approach and methods such as analytical-synthetic, historical-logical and inductive-deductive